Mortality from pandemic A/H1N1 2009 influenza in England: public health surveillance study. (10th December 2009) - Donaldson, Liam J; Rutter, Paul D; Ellis, Benjamin M; Greaves, Felix E C; Mytton, Oliver T; Pebody, Richard G; Yardley, Iain E
Abstract : Objective To establish mortality from pandemic A/H1N1 2009 influenza up to 8 November 2009. Design Investigation of all reported deaths related to pandemic A/H1N1 in England. Setting Mandatory reporting systems established in acute hospitals and primary care. Participants Physicians responsible for the patient. Main outcome measures Numbers of deaths from influenza combined with mid-range estimates of numbers of cases of influenza to calculate age specific case fatality rates. Underlying conditions, time course of illness, and antiviral treatment. Results With the official mid-range estimate for incidence of pandemic A/H1N1, the overall estimated case fatality rate was 26 (range 11-66) per 100 000. It was lowest for children aged 5-14 (11 (range 3-36) per 100 000) and highest for those aged ≥65 (980 (range 300-3200) per 100 000). In the 138 people in whom the confirmed cause of death was pandemic A/H1N1, the median age was 39 (interquartile range 17-57). Two thirds of patients who died (92, 67%) would now be eligible for the first phase of vaccination in England. Fifty (36%) had no, or only mild, pre-existing illness. Most patients (108, 78%) had been prescribed antiviral drugs, but of these, 82 (76%) did not receive them within the first 48 hours of illness. Conclusions Viewed statistically, mortality in this pandemic compares favourably with 20th century influenza pandemics. A lower population impact than previous pandemics, however, is not a justification for public health inaction. Our data support the priority vaccination of high risk groups. We observed delayed antiviral use in most fatal cases, which suggests an opportunity to reduce deaths by making timely antiviral treatment available, although the lack of a control group limits the ability to extrapolate from this observation. Given that a substantial minority of deaths occur in previously healthy people, there is a case for extending the vaccination programme and for continuing to make early antiviral treatment widely available.